2020
DOI: 10.1021/acs.cgd.0c00953
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into Single-Crystal Silver Dendrite Formation and Growth Mechanisms

Abstract: Single-crystal silver dendrite structures, which possess a high surface area along with narrow gaps and sharp edges, have been widely explored as surface enhanced Raman scattering substrates and for catalytic and biosensing applications. With one of the simplest galvanic reactions, the reaction of AgNO3 with Cu, Ag dendrites can easily be produced. Here, we report new findings about this reaction and dendrite growth mechanisms. A series of experiments revealed a much more complicated reaction mechanism: metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…On the other hand, the OA mechanism can lead to the self-alignment process of adjacent Ag particles, resulting in the joining of Ag particles along the preferential orientation growth. However, it is also found that Ag dendrites are formed on the PI surface away from the Cu sheet, indicating that the particle-mediated growth process has to be taken an account . Moreover, by tuning different parameters including Ag + ion concentration, amount of reducing agents, and temperature, the morphology of the produced structure still resembles a dendrite with different size and dense Ag branches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the OA mechanism can lead to the self-alignment process of adjacent Ag particles, resulting in the joining of Ag particles along the preferential orientation growth. However, it is also found that Ag dendrites are formed on the PI surface away from the Cu sheet, indicating that the particle-mediated growth process has to be taken an account . Moreover, by tuning different parameters including Ag + ion concentration, amount of reducing agents, and temperature, the morphology of the produced structure still resembles a dendrite with different size and dense Ag branches.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is also found that Ag dendrites are formed on the PI surface away from the Cu sheet, indicating that the particle-mediated growth process has to be taken an account. 24 Moreover, by tuning different parameters including Ag + ion concentration, amount of reducing agents, and temperature, the morphology of the produced structure still resembles a dendrite with different size and dense Ag branches. Therefore, these results demonstrate that the morphology of the in situ grown Ag film can be manipulated by different reductants and reduced time.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[56][57][58] Such conditions are difficult to achieve in homogeneous solutions based on wet chemical synthesis. 39 However, when the reaction occurs at the interface of a solid-phase reducing agent, the nonequilibrium conditions are easily realized. 59 In the present study, the solid-phase alginate hydrogel beads acted as the reducing agent and Ag atoms were generated on the surface of the alginate hydrogel beads irradiated with UV light.…”
Section: Growth Mechanism Of 2d Ag Dendritesmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38] However, most of these methods require expensive and/or sophisticated equipment, a long reaction time, an elevated reaction temperature, complex synthesis steps, specic additives such as surfactants, and a supplementary etching process to remove the templates or surfactants. 39,40 Therefore, synthesizing Ag dendrites through a simple synthetic method without surfactants or harmful materials and under ambient conditions remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, silver’s electronic and optical properties are readily controlled by size and shape. So, to fabricate these silver dendrites, long-duration processes such as photoreduction in the presence of ultraviolet irradiation, and the use of sacrificial metals such as copper and zinc in the galvanic replacement process, , has been well established. Although these processes can produce large amounts of silver dendrites, they cannot ascertain control over the direction of growth.…”
Section: Introductionmentioning
confidence: 99%